2014
DOI: 10.1177/1088357614549317
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Gender and Age on Stress and Emotional Distress in Adults With Autism Spectrum Disorder

Abstract: One hundred nine people with autism spectrum disorder (ASD) completed the Depression Anxiety Stress Scales (DASS), and Stress Survey Schedule (SSS). Compared with Australian norms for DASS depression, anxiety, and stress, both males and females with ASD showed elevated scores. Females aged 25 to 44 years scored significantly higher on the DASS depression subscale than same aged males and younger males and females. Significant gender and age differences were evident on SSS subscales. In comparison with males, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 53 publications
4
41
0
Order By: Relevance
“…Research into the experiences of girls with autism is limited, due partly to the predominance of male diagnoses, but also since the majority of studies focus on gender differences from a biogenic viewpoint or using quantitative methodology (e.g. Baron-Cohen 2002;Dworzynski et al, 2012;Hartley and Sikora 2009;McGillivray and Evert 2014;Wing 1981), which while valuable do not offer the rich understanding of their perceptions of friendship that qualitative studies can elicit. In addition, although in recent years qualitative studies have been published (Cridland et al 2014;Sedgewick et al 2016;Tierney, Burns, and Kilbey 2016), they haven't located girls' experiences alongside their parents' and across school setting types.…”
Section: Introductionmentioning
confidence: 99%
“…Research into the experiences of girls with autism is limited, due partly to the predominance of male diagnoses, but also since the majority of studies focus on gender differences from a biogenic viewpoint or using quantitative methodology (e.g. Baron-Cohen 2002;Dworzynski et al, 2012;Hartley and Sikora 2009;McGillivray and Evert 2014;Wing 1981), which while valuable do not offer the rich understanding of their perceptions of friendship that qualitative studies can elicit. In addition, although in recent years qualitative studies have been published (Cridland et al 2014;Sedgewick et al 2016;Tierney, Burns, and Kilbey 2016), they haven't located girls' experiences alongside their parents' and across school setting types.…”
Section: Introductionmentioning
confidence: 99%
“…The respondents are asked to rate the intensity of their stress reaction in common daily activities, divided into eight categories: (i) Changes and Threats, (ii) Anticipation/Uncertainty, (iii) Unpleasant Events, (iv) Pleasant Events (such as presents or birthday parties), (v) Sensory/Personal Contact, (vi) Food-Related Activity, (vii) Social/Environment Interactions and (viii) Ritual-Related Stress (Groden et al, 2001). In two studies, Cronbach’s alpha was reported (Bishop-Fitzpatrick et al, 2017a; McGillivray & Evert, 2018), indicating excellent internal consistency of the questionnaires’ total score (α = 0.96-0.97). The internal consistency of the subscales, ranging from 0.58 to 0.89, reported in the study of McGillivray and Evert (2018) was similar to the internal consistency values of the original version by Groden et al (2001).…”
Section: Resultsmentioning
confidence: 99%
“…In two studies, Cronbach’s alpha was reported (Bishop-Fitzpatrick et al, 2017a; McGillivray & Evert, 2018), indicating excellent internal consistency of the questionnaires’ total score (α = 0.96-0.97). The internal consistency of the subscales, ranging from 0.58 to 0.89, reported in the study of McGillivray and Evert (2018) was similar to the internal consistency values of the original version by Groden et al (2001). One study compared the scores on the SSS of adults with ASD to those of typical peers and found statistically significant differences, indicating a higher stress intensity for adults with ASD (Bishop-Fitzpatrick et al, 2017a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations